2013
DOI: 10.12659/msmbr.883726
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucagon-like peptide-1 receptor stimulation and blockade on food consumption and body weight in rats treated with a cannabinoid CB1 receptor agonist WIN 55,212-2

Abstract: BackgroundGlucagon-like peptide-1 (GLP-1) and endocannabinoids are involved in appetite control. Recently we have demonstrated that cannabinoid (CB)1 receptor antagonist and GLP-1 receptor agonist synergistically suppress food intake in the rat. The aim of the present study was to determine the effects of GLP-1 receptor stimulation or blockade on feeding behavior in rats treated with WIN 55,212-2, a CB1 receptor agonist.Material/MethodsExperiments were performed on adult male Wistar rats. In the first experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The majority of previous evidence suggest that orexigenic actions of cannabinoids are linked to CB 1 receptors located in the hypothalamus [32][33][34] , with some research also implicating the role of CB 2 receptors in increased food consumption 35 . A close relationship also exists between the endocannabinoid system and endocrine pathways involved in metabolic regulation and food seeking behaviors [36][37][38][39] . For example, investigators found that orexigenic effects of systemically administered ghrelin (also known as the "hunger hormone") were abolished in CB 1 receptor knockout mice 40 , and pharmacological blockade of the CB 1 receptor, via rimonabant administration, attenuated ghrelin-induced activation of the mesolimbic dopamine systema key pathway involved in reward processing 41 .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of previous evidence suggest that orexigenic actions of cannabinoids are linked to CB 1 receptors located in the hypothalamus [32][33][34] , with some research also implicating the role of CB 2 receptors in increased food consumption 35 . A close relationship also exists between the endocannabinoid system and endocrine pathways involved in metabolic regulation and food seeking behaviors [36][37][38][39] . For example, investigators found that orexigenic effects of systemically administered ghrelin (also known as the "hunger hormone") were abolished in CB 1 receptor knockout mice 40 , and pharmacological blockade of the CB 1 receptor, via rimonabant administration, attenuated ghrelin-induced activation of the mesolimbic dopamine systema key pathway involved in reward processing 41 .…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Radiszewska et al on Wistar rats, a stimulation of peripheral CB 1 R by its agonist (WIN 55,212-2) had an anorexigenic effect and induced activity of exendin-4, a peptide agonist of the glucagon-like-peptide 1 [ 216 ]. It suggests a double activity of the ECS and could be used in the pharmacotherapy of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these data, studies have shown interactions between endocannabinoid-like molecules and GLP-1 [145]. Preclinical results demonstrated that CB1 antagonism could enhance GLP-1 receptor agonists activity [146] and improve GLP-1R mediated insulin secretion [147], suggesting that new drugs acting on the ECS system may have a synergic effect and ameliorate the results obtained with liraglutide treatment. For these reasons, research on anti-obesogenic drugs acting on the ECS is still an option that must not be discarded.…”
Section: Endocannabinoid System As a Pharmacological Target For Obesity And Food Addictionmentioning
confidence: 93%